Patient Perspectives on the Impact of Living With Hidradenitis Suppurativa: Results From the Global ‘HS Uncovered’ Burden of Disease Survey - Kokolakis, Georgios; Vilarrasa, Eva; Garg, Amit; Alarcon, Ivette; Go, Mei; Newbold, Gillian; Mamareli, Aikaterini; Richardson, Craig; McGrath, Barry M.; Guillem, Philippe (JEADV clinical practice, 2025)
ABSTRACT Background Hidradenitis suppurativa (HS) is a chronic, painful inflammatory skin disease. There is a need to evaluate how patients experience their disease. Objectives The HS Uncovered survey was conducted to understand patient activation, the patient journey and burden of disease. Methods HS Uncovered was a real‐world, quantitative, online survey completed by adults who self‐reported a diagnosis/suspected diagnosis of HS. The survey included patient‐reported outcome measures (PROMs) and non‐PROM‐related questions and was conducted between December 2022 to March 2023 in six countries (US, UK, Germany, France, ltaly, Spain). PROMs included the Patient Activation Measure (PAM13; primary endpoint), Dermatology Life Quality Index (DLQI), Work Productivity and Activity Impairment (WPAI) and Hospital Anxiety and Depression Scale (HADS) tools (Spain excluded from PROM analyses). Results Overall, 656 participants were included (N = 505, diagnosed HS; N = 151, suspected HS). Of 425 diagnosed participants, 66% reported high (level 3/4) PAM13 scores. A very large (DLQI score 11–20) and extremely large (DLQI score 21–30) effect of HS on QoL was reported by 41% and 28% of participants, respectively. A very large to extremely large effect of HS on QoL (DLQI score 11–30) was reported by 67% and 73% of patients with level 3 and 4 PAM13 scores, respectively. Overall, 53% and 29% of diagnosed participants reported abnormal anxiety and depression, respectively. The percentage of work impairment due to HS in employed diagnosed participants (N = 302) was 52%. Of diagnosed females, 52% considered HS a concern for family planning. Overall (N = 656), 58% of participants considered pain relief the most important treatment feature. Conclusions Despite participants having high activation levels, HS had a negative impact on QoL, mental health, work and activity. There is an unmet need for effective treatments that provide sustained pain reduction and improve work productivity in HS. Summary Why was the study undertaken? ◦ To understand the impact and burden of hidradenitis suppurativa (HS) from the patient's perspective, to assess patients' level of knowledge, skills and confidence to make effective decisions about their condition and to understand the patient's journey through the healthcare system. What does this study add? ◦ Over 60% of people living with HS had a high activation level, indicating they are taking action and trying to manage their own health. Despite this, HS had a negative impact on quality of life, mental health, and work productivity. What are the implications of this study for disease understanding and/or clinical care? ◦ Improvements are needed in the patient journey to ensure people living with HS receive a timely diagnosis and access to healthcare professionals and effective disease and comorbidity management. There is an unmet need for effective treatments.